Possession and using land as an owner would - Atmaz Al-Sibaie, J (Sweet and Maxwell, 2024)
Accounts of possession of land often emphasise the physical occupation of the possessor. This article argues that this focus is incorrect. It shows that one can possess land by using it as an owner would without exercising physical control, for example, by letting it out for value.